Farmer's attitude and values for wetland conservation and climate change in Phobjikha velley - Tamang, Bina. (CNR, Lobesa : Tamang, Bina, 2019)
Includes acknowledgment, Abstract, references (page 25-28) & Annexure(x-xiv).
Keywords: Climate change in Phobjikha velley